OPEN-AIR SUN DRYING: THE EFFECT OF PRETREATMENT ON DRYING KINETIC OF CHERRY TOMATO - Ismail, Osman; Akyol, Emel (YILDIZ TECHNICAL UNIV, 2016)
In this study, the effects of open-air sun drying and pretreatment on drying characteristic of cherry tomato (Lycopersicum esculentum) were investigated. Drying times were determined as 26 and 22 h for natural and pretreated, respectively. The pretreated samples were dried in slightly shorter time than the natural samples. The drying process took place in the falling rate period. Different seven theoretical drying models were applied to experimental data of falling rate periods. All the models were compared according to statistical parameters; i.e. model efficiency (R-2), chi-square (.2) and root mean square error (RMSE). It was observed that Verma et al. model among the models used is best mathematical model represented the open-air sun drying behavior of cherry tomatoes. The best chroma (C*) value were obtained in pre-treatment dried cherry tomatoes.
Keywords: Cherry tomatoes; open-sun drying; pretreatment; chroma; modelling; CONVECTIVE CYCLONE DRYER; SOLAR DRYER; TUNNEL DRYER; MINT LEAVES; DEHYDRATION; SLICES; QUALITY; PARAMETERS; COLOR; Engineering